2012
DOI: 10.1016/j.febslet.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gene transfer between the Bacteroidetes and Acidobacteria: The case of α‐l‐rhamnosidases

Abstract: a b s t r a c t a-L-Rhamnosidases catalyze the hydrolysis of the terminal a-L-rhamnose residues in various carbohydrates. The catalytic domains in most of these enzymes belong to the families GH78 and GH106 of glycoside hydrolases. In this study, we show that almost all genes encoding the GH78-and GH106-containing proteins from members of the poorly characterized bacterial phylum Acidobacteria originated from precursors belonging to the phylum Bacteroidetes. Members of the Acidobacteria and Bacteroidetes displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Consistent with those of Kolton et al [27] and Xu et al [63], our findings revealed that the relative abundance of Bacteroidetes in biochar-treated soil under R. solanacearum infection (Rs + BC) significantly increased compared with the no biochar treatments ( Figure 5). Bacteroidetes are generally specialized in the degradation of organic matter, promote plant growth, and increase their resistance to environmental stress [64,65]. Our results also indicated that the relative abundances of Chitinophaga, Flavitalea, Adhaeribacter, Pontibacter, Pedobacter, and Ohtaekwangia at the genus level, which are bioremediators of hydrocarbons [49], were significantly increased by biochar amendment (Figure 6).…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with those of Kolton et al [27] and Xu et al [63], our findings revealed that the relative abundance of Bacteroidetes in biochar-treated soil under R. solanacearum infection (Rs + BC) significantly increased compared with the no biochar treatments ( Figure 5). Bacteroidetes are generally specialized in the degradation of organic matter, promote plant growth, and increase their resistance to environmental stress [64,65]. Our results also indicated that the relative abundances of Chitinophaga, Flavitalea, Adhaeribacter, Pontibacter, Pedobacter, and Ohtaekwangia at the genus level, which are bioremediators of hydrocarbons [49], were significantly increased by biochar amendment (Figure 6).…”
Section: Discussionsupporting
confidence: 53%
“…The extended contig VISS3_113 (VISS3_041 1 VISS3_113; 64.5 kbp) encodes a PUL with two predicted GH106 alpha-rhamnosidase genes (ORFs VISS3_113_01, VISS3_113_16). Alpha-L-rhamnosidases are known to cleave terminal alpha-L-rhamnose from cell wall polysaccharides of plants (in rhamnogalacturonans) and green algae (ulvans, a family of sulfated xylorhamnoglucuronans) (Lahaye and Robic, 2007;Popper et al, 2011;Naumoff and Dedysh, 2012;Martin et al, 2014). This PUL also contains two carbohydrate sulfatase genes (ORFs VISS3_113_14, VISS3_113_17) and a nonclassified GH (ORF VISS3_113_10), which could act in synergy with the GH106 enzymes in the degradation of sulfated rhamnose-containing polysaccharides.…”
Section: Additional Puls From Bplr Stationmentioning
confidence: 99%
“…Actinobacteria can survive in the soil environment and are thought to be beneficial in the agricultural soils (Marta et al 2014). Acidobacteria also display a functional capability and specialize on degradation of plantderived organic matter (Naumoff and Dedysh 2012). Members of Bacteroidetes, which were often involved in the degradation of bio-macromolecules such as proteins, cellulose, chitin, pectin, agar, starch (Hugenholtz et al 1998), and more recalcitrant compounds (Lipson and Schmidt 2004), increased proportionally in the L-OM treatment.…”
mentioning
confidence: 99%